Criminal responsibility and political responsibility: convergences and divergences in the fight against political corruption - Alves Magalhães, Gustavo (2024)
This article initially makes a distinction between criminal responsibility and political responsibility. From this, it is discussed how the development of political responsibility in the sphere of political parties, especially by a compliance program, can help to strengthen a culture of integrity in these associations, to contain movements of judicialization of politics and politicization of justice and, finally, to reinvigorate the credibility of these entities.